DIPLOMASI STRATEGI MARITIM PENCEGAHAN PEMBAJAKAN DI ALUR LAUT KEPULAUAN INDONESIA MENYONGSONG INDONESIA EMAS 2045 - Novitasari, Destin; Rudiyanto, Rudiyanto; Yusnaldi, Yusnaldi; Widodo, Pujo; Juni Risma Saragih, Herlina; Suwarno, Panji; Yudho Prakoso, Lukman (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2024)
Piracy at sea is a crime committed by a group of people to take and seize and sabotage things related to the world of shipping, especially ships. This is one of the threats that can hinder the realisation of Indonesia's vision in welcoming the golden Indonesia 2045 considering the importance of Indonesia's maritime sector. In facing the challenges of preventing piracy in the Indonesian Archipelago Sea Route, maritime strategy diplomacy is the key. The purpose of this paper is to analyse and formulate an effective maritime diplomacy strategy in preventing piracy in the Indonesian Archipelago Sea Route (ALKI) and to examine the link between piracy prevention efforts and the long-term vision of "Golden Indonesia 2045". The main focus is on how maritime diplomacy can be an effective instrument in building regional and international cooperation. The method used is descriptive qualitative method, which is an in-depth and detailed understanding of Maritime Strategy Diplomacy and piracy prevention in the Indonesian Archipelago Sea Route by involving literature study, policy analysis, and case studies to gain contextual understanding. This paper also highlights the importance iof isynergy between military power, diplomacy, and multilateral cooperation to achieve strategic objectives. As such, this paper highlights the importance of synergy between military power, diplomacy, and multilateral co-operation to achieve strategic objectives. Thus, this scientific paper highlights the importance of strategic integration between aspects of maritime diplomacy and Indonesia's long-term aspiration of Indonesia Golden 2045 in ensuring maritime sovereignty and security in Indonesia.